Evaluación de los contenidos curriculares y su incidencia en el aprendizaje de los/as estudiantes de octavo, noveno y décimo año de educación básica del Colegio Técnico Puyango de la ciudad de Alamor, cantón Puyango provincia de Loja, período 2011-2012. Lineamientos alternativos - Quizhpe Cuenca, Sandra Elizabeth (2012)
The work presented investigates the "Evaluation of curriculum contents and its impact on in the learning of the Eighth, Ninth and Tenth Year of Basic Education of Technical Puyango high school of the Alamor City, Puyango Canton Loja Province, Period 2011 - 2012. Alternative Guidelines". The fundamental problem is based in the question How does the evaluation of the curriculum contents influence in the learning of the students of Eighth, Ninth and Tenth Year of Basic Education of Technical Puyango high school of the Alamor city, Puyango canton Loja Province ?, considering that the evaluation of the various curriculars contents should give in multiple forms, some more complex than others, in order to enhance the conceptual learning, procedural and attitudinal, that in leave aside the tendency to confuse the evaluation as an activity accreted to be conceived from this optic how result, but not as the process this analysis itself notes the need of a change imperative, substantially in the forms of teaching, learning, and consequently in the form of evaluate that begin inexctricably linked the teaching-learning process the evaluation of contents proposed in the curriculum influences carefully in the learning of themselves. Therefrom realty the hypothesis that support the researh: The evaluation of the curriculum contents that makes the teacher does not contribute to the learning of concepts, the following hypothesis states that; the evaluation of curriculum contents procedural that teachers apply contributes partially to the achievement of learners of procedures, and finally the application of the evaluation of the curricular contents, attitudinal by the teachers in its most do not develop a learning of attitude. Then the respective analysis of each one of the hypothesis is verified that the teachers of the Technical "Puyango" high school, have limited knowledge about techniques and procedures to evaluate curriculum contents and still maintain a traditionalist view of the evaluation thereof, before it is posed alternative guidlines as a proposed of innovation and professional development, that with suitable application in the classroom permit strengthen the learnings and in if to improve the practice teacher’s evaluate.